Evidence for the triadic model of adolescent brain development: Cognitive load and task-relevance of emotion differentially affect adolescents and adults - Mueller, Sven C. (Dev Cogn Neurosci, 2017)
In adults, cognitive control is supported by several brain regions including the limbic system and the dorsolateral prefrontal cortex (dlPFC) when processing emotional information. However, in adolescents, some theories hypothesize a neurobiological imbalance proposing heightened sensitivity to affective material in the amygdala and striatum within a cognitive control context. Yet, direct neurobiological evidence is scarce. Twenty-four adolescents (12–16) and 28 adults (25–35) completed an emotional n-back working memory task in response to happy, angry, and neutral faces during fMRI. Importantly, participants either paid attention to the emotion (task-relevant condition) or judged the gender (task-irrelevant condition). Behaviorally, for both groups, when happy faces were task-relevant, performance improved relative to when they were task-irrelevant, while performance decrements were seen for angry faces. In the dlPFC, angry faces elicited more activation in adults during low relative to high cognitive load (2-back vs. 0-back). By contrast, happy faces elicited more activation in the amygdala in adolescents when they were task-relevant. Happy faces also generally increased nucleus accumbens activity (regardless of relevance) in adolescents relative to adults. Together, the findings are consistent with neurobiological models of adolescent brain development and identify neurodevelopmental differences in cognitive control emotion interactions.